2021
DOI: 10.1186/s12931-021-01726-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bronchoalveolar lavage lymphocytosis on the effects of anti-inflammatory therapy in idiopathic non-specific interstitial pneumonia, idiopathic pleuroparenchymal fibroelastosis, and unclassifiable idiopathic interstitial pneumonia

Abstract: Background Idiopathic non-specific interstitial pneumonia (iNSIP), idiopathic pleuroparenchymal fibroelastosis (iPPFE), and unclassifiable idiopathic interstitial pneumonia (IIP) are IIPs with chronic fibrotic phenotypes, and unlike idiopathic pulmonary fibrosis, they have often been treated with anti-inflammatory drugs, including corticosteroids and immunosuppressants. However, the impact of bronchoalveolar lavage (BAL) lymphocytosis on the effects of anti-inflammatory therapy has never been e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
4
0
4
Order By: Relevance
“… 5 , 6 , 27 Given that progression and relapse are associated with grave outcomes, the identification of their predictive factors is important for improving outcomes. Several multicenter survey studies have suggested the presence of ANA, low BAL lymphocyte count (⩽15%), or long duration of symptoms as possible risk factors for unresponsiveness to treatment in fibrotic ILD or idiopathic NSIP; 28 , 29 however, the predictive factors for progression or relapse in fibrotic NSIP have not been established. To the best of our knowledge, this is the first study to investigate the risk factors for progression or relapse in biopsy-confirmed fibrotic NSIP based on distinct criteria.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 , 27 Given that progression and relapse are associated with grave outcomes, the identification of their predictive factors is important for improving outcomes. Several multicenter survey studies have suggested the presence of ANA, low BAL lymphocyte count (⩽15%), or long duration of symptoms as possible risk factors for unresponsiveness to treatment in fibrotic ILD or idiopathic NSIP; 28 , 29 however, the predictive factors for progression or relapse in fibrotic NSIP have not been established. To the best of our knowledge, this is the first study to investigate the risk factors for progression or relapse in biopsy-confirmed fibrotic NSIP based on distinct criteria.…”
Section: Discussionmentioning
confidence: 99%
“…In der Studie von Yamagata et al war eine BAL-Lymphozytose < 15 % ein unabhängiger negativer Prädiktor für das Ansprechen auf antiinflammatorische Therapie 104 . In einer retrospektiven Studie bei 91 Patienten mit fibrotischer EAA war eine BAL-Lymphozytose < 20 % gemeinsam mit Honigwabenmuster im HRCT mit fehlendem Ansprechen auf die Steroidtherapie assoziiert 117 .…”
Section: Diskussion Und Wertung Einzelner Medikamentöser Verfahrenunclassified
“…Bei vielen Erkrankungen nimmt sie mit fortschreitender Fibrosierung eher ab. Eine retrospektive Studie aus Japan zeigte bei Patienten mit chronisch fibrotischen ILDs (37 iNSIP, 16 iPPFE, 133 unclassifiable IIP), dass eine BAL-Lymphozytose nur bei den antiinflammatorisch behandelten Patienten mit einer günstigeren Prognose assoziiert war, nicht jedoch bei den unbehandelten Patienten 104 .…”
Section: Diskussion Und Wertung Einzelner Medikamentöser Verfahrenunclassified
See 1 more Smart Citation
“…darauf hinweisen, dass die Krankheit auf anti-inflammatorische Therapie ansprechen bzw. eine günstige Prognose aufweisen wird [104][105][106]. Bei Patient:innen mit systemischen Autoimmunkrankheiten korreliert eine leicht-bis mittelgradige Neutrophilie eher mit fortgeschrittener fibrotischer ILD [107].…”
Section: Habitusunclassified